Study the Effect of Smoking on the Potential of Human Resources - Sunardi; Kurniawan, Muhammad Rezki Agus; MT Safirin (Future Science)
Human resources have an important role in development so that the potential need to be developed. Fatigue is a normal condition in everyday life. In general, fatigue can be divided into two namely, physical fatigue (physical fatigue) and mental fatigue (mental fatigue). Many factors can cause fatigue in humans, one of which is smoking behavior. Smoking in adolescence, especially working age will disrupt fitness, especially cardiorespiratory endurance. One method that can support this research is the Response Surface Methodology method. The results showed that smoking for nine years with moderate consumption of cigarettes at the age of work did not affect physical or mental fatigue, but there was a tendency to increase a little mental and physical fatigue. Improved predictability can significantly reduce physical endurance.